Comparison between Islamic educational philosophy and secular western educational philosophy Ahmad tafsir perspectiveComparison between Islamic educational philosophy and secular western educational philosophy Ahmad tafsir perspective - Ummu Habibah Refrinur; Amin Fauzi (JPP (Jurnal Pendidikan dan Pembelajaran), 2025)
Education is an important aspect in shaping human character and intelligence. However, the modern education system often experiences a separation between science and moral values, which has an impact on identity crises as well as spiritual damage. Islamic philosophy of education is based on the values of revelation and reason, while secular Western philosophy of education emphasizes more on rationality in the absence of spiritual values. This study aims to compare in depth the two educational philosophies based on Ahmad Tafsir's thoughts. This research uses a qualitative method with a library research approach, which is sourced from the works of Ahmad Tafsir and other supporting literature. The results of the study show that Ahmad Tafsir emphasizes the importance of integration between science and the value of faith in the education system. He considers that the failure of the Western secular education system in shaping the entire human race is due to the loss of the spiritual dimension. In conclusion, Ahmad Tafsir's thinking offers a relevant alternative educational paradigm, namely by making revelation the main foundation and without ruling out reason. The balance between revelation and reason is the ultimate foundation in shaping man intellectually, morally, and spiritually.